О связи смертности приплода котиков (Collorhinus ursinus) (Mammalia, Otariidae) на лежбищах о. Медный с учетом и мечением - Челноков, Ф.Г. (Вестник зоологии, 1978)
The data on abundance and mortality of fur seal pups are given for south-eastern rookery of Medny Island (the Commander Islands) for the period of 1966-1975. For the time from mid June to late July mortality accounted for 3.2-11.6% of the number of new-born pups. During the time of counting the mortality of the pups did not exceed 3% and in some cases it was not recorded at all. In August pups' death sharply decreased. The processes of counting and tagging have no considerable influence on fur seals mortality.